The Effect Of Up And Down Standard Exercise On The Results Of The Squat Style Lop On Extracurricular Participants Of Sma Negeri 6 South Bengkulu - Syafrial Syafrial; Arwin Arwin; Rati Marya Kontesa (UNIB Press, 2021)
This research purpose to know the influence practice up and down stairs to result long jump style squat, this research was conduct on the square SMA Negeri 6 Bengkulu Selatan.in student follow extracullicular long jump, this study uses an experimental method, the design used is the design of one group pretest-posttest, that is pretest before given treatment and posttest after being treated. the treatment given there is one exercise up and down stairs. Data collection techniques in this study with the direct test method that is using the long jump, statistical prerequite tests meet5 homogeneous requirements and normally distribute data based on statistical calculations obtained from the data count = 5.664> T_(table= )2.064 with the level = 0.05. The result of this study indicates on the ability of the extracurricular SMA Negeri 6 Bemgkulu Selatan.